5-PGDH expression in breast cancer cells - M. A. Taipov; Z. N. Nikiforova; O. M. Pavlova; I. A. Kudryavtsev; N. Ye. Arnotskaya; V. Ye. Shevchenko (ABV-press, 2014)
This paper analyzes 15-PGDH gene expression in the human breast cancer (BC) cell liness and describes the molecular principles through which the expression of the enzyme 15-PGDH is controlled in the tumor cells with a varying metastatic potential. There is an inverse correla- tion of 15-PGDH gene expression with COX-2 expression and the metastatic potential of tumor cells. Investigation of mechanisms for 15-PGDH regulation opens up new vistas and possibilities for the design of effective drugs for the targeted therapy of metastatic forms of BC.